Phytogenic Products and Phytochemicals as a Candidate Strategy to Improve Tolerance to Coronavirus - Attia, Youssef A.; Alagawany, Mahmoud M.; Farag, Mayada R.; Alkhatib, Fatmah M.; Khafaga, Asmaa F.; Abdel-Moneim, Abdel-Moneim Eid; Asiry, Khalid A.; Mesalam, Noura M.; Shafi, Manal E.; Al-Harthi, Mohammed A.; Abd El-Hack, Mohamed E. (Frontiers in Veterinary Science, 2020)
Coronaviruses are the causative agents of many infectious diseases in human and animals. These included severe acute respiratory syndrome (SARS), avian infectious bronchitis (IBV) in poultry, Middle East respiratory syndrome (MERS), and coronavirus disease 2019 (COVID-19) in humans. These results had considerable death burdens and negative influences on social–economic life. Since the appearance of the outbreak of the COVID-19 pandemic, continuous investigations have been carried out by researchers to find active compounds, mainly from plants, as natural sources, that could inhibit or stop the proliferation of the causative agent of COVID-19 (SARS-CoV-2). The most common symptoms caused by infections with COVID-19 can include cough, fever, and sore throat. Nevertheless, there is a shortage of active antiviral compounds for treating different strains of coronavirus. Herbal medicine is a class of medication that originates from nature and is aimed at decreasing the use of preservatives, excipients, or other additives and, consequently, lesser side effects. The rapid spread of COVID-19 infection besides the lack of knowledge about any treatments and the growing concern of the public from the virus directed us toward writing this review article in an aim to provide alternatives to the allopathic medicine use. There is a wealth of chemical diversity in the naturally existing compounds, including their antiviral activities, which may encourage their utilization as therapeutics against viral infections, including coronaviruses. The majority of publications on the herbal remedies of coronavirus, MERS, or SARS focused primarily on the use of polar compounds. These substances displayed encouraging inhibitory influences on coronavirus in humans. These include psoralidin, scutellarein, silvestrol, tryptanthrin, caffeic acid, quercetin, myricetin, saikosaponin B2, griffithsin (lectins), and isobavachalcone. Some other agents like lycorine may be useful, if the antiviral activity is obtained by concentrations below the toxic plasma levels. According to the available literatures, the most promising inhibitors of coronaviruses are polyphenolic compounds, which are small molecules with conjugated fused ring structures.